2007
DOI: 10.1038/sj.mp.4002099
|View full text |Cite
|
Sign up to set email alerts
|

The mood stabilizers lithium and valproate selectively activate the promoter IV of brain-derived neurotrophic factor in neurons

Abstract: Brain-derived neurotrophic factor (BDNF) has been strongly implicated in the synaptic plasticity, neuronal survival and pathophysiology of depression. Lithium and valproic acid (VPA) are two primary mood-stabilizing drugs used to treat bipolar disorder. Treatment of cultured rat cortical neurons with therapeutic concentrations of LiCl or VPA selectively increased the levels of exon IV (formerly rat exon III)-containing BDNF mRNA, and the activity of BDNF promoter IV. Surprisingly, lithium-or VPA-responsive ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
205
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(221 citation statements)
references
References 48 publications
10
205
0
2
Order By: Relevance
“…Work has also shown that site-specific infusion of Bdnf into the PFC during early abstinence, but not following protracted abstinence, attenuates subsequent cue-induced reinstatement responding (Berglind et al 2007) and normalizes neuroadaptations that are associated with the high levels of cocaine-seeking (Whitfield et al 2011). This idea of time-dependent upregulation of Bdnf is also supported by our current findings showing that when provided beginning during early abstinence, HDAC inhibition, which is known to increase Bdnf exon IV expression (Yasuda et al 2009), mimicked both the behavioral and molecular effects of wheel running. A caveat to this idea, however, is that wheel running did not increase Bdnf exon IV expression among saline controls.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Work has also shown that site-specific infusion of Bdnf into the PFC during early abstinence, but not following protracted abstinence, attenuates subsequent cue-induced reinstatement responding (Berglind et al 2007) and normalizes neuroadaptations that are associated with the high levels of cocaine-seeking (Whitfield et al 2011). This idea of time-dependent upregulation of Bdnf is also supported by our current findings showing that when provided beginning during early abstinence, HDAC inhibition, which is known to increase Bdnf exon IV expression (Yasuda et al 2009), mimicked both the behavioral and molecular effects of wheel running. A caveat to this idea, however, is that wheel running did not increase Bdnf exon IV expression among saline controls.…”
Section: Discussionsupporting
confidence: 76%
“…Although NaBu is a non-specific HDAC inhibitor, and in this study its effects were examined following systemic administration, evidence suggests that inhibition of HDAC activity affects the expression of only approximately 2% of genes (Van Lint et al 1996;Davie et al 2003). Evidence also shows that Bdnf exon IV is activated in cortical regions including the PFC following systemic NaBu administration (Yasuda et al 2009), and that in the cortex, exon IV-dependent Bdnf transcription accounts for the majority of the neuronal activity-induced Bdnf expression (Tao et al 2002;Timmusk et al 1994). While these results provide support for the idea that epigenetic regulation of Bdnf likely mediates the efficacy of NaBu treatment, further work is needed to rule out other mechanisms (e.g., DAergic signaling).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain-derived neurotrophic factor (BDNF) supports the survival of select differentiated neurons [32,33] and encourages the growth and differentiation of new neurons and synapses. Addition of VPA to cultured rat cortical neurons induces BDNF messenger RNA [34] and induces vascular endothelial growth factor, angiogenesis, and neurogenesis in vivo [35,36]. In a screen of small molecules structurally related to known HDAC inhibitors a compound referred to as crebinostat, for its ability to concomitantly activate cyclic adenosine monophosphate response element binding-mediated transcription, was identified [37].…”
Section: Transcriptional Effectsmentioning
confidence: 99%